PEMETAAN KECERDASAN MELALUI TES DAN SEMINAR MULTIPLE INTELLIGENCE DI PANTI ASUHAN - Kurniawati, Meike; Ninawati (Jurnal Serina Abdimas, 2024)
Human intelligence is not limited to one area, but consists of several intelligences or known as multiple intelligences. There are 8 types of intelligence according to Howard Gardner, namely: Linguistic Intelligence; Logical mathematical intelligence; Musical intelligence; Kinesthetic intelligence; Visual spatial intelligence; Interpersonal intelligence; and Naturalist intelligence. The intelligence that a person has needs to be developed optimally, for self-development and future planning. To be able to develop this intelligence, a person needs to first find and recognize what abilities he has, one way is to test Multiple intelligence. Seeing the importance of recognizing the intelligence that is possessed, the Faculty of Psychology - Tarumanagara University - Jakarta in collaboration with Panti Asuhan X (Mitra) held a Multiple intelligence test and seminar. The purpose of the activity is: to map the intelligence of participants in addition to the personal interests of participants and Partners. so that Partners can create the right learning program in addition to the main learning at school. The results of this test will later be able to describe the Multiple intelligence possessed by each participant. The 3 highest results are the 3 dominant Multiple intelligences. From the evaluation of the activities carried out, the participants gave test imonies that the 3 largest scores from the test were in accordance with the participants' conditions, and were further strengthened by the test scores obtained. Mitra also explained that many of the participants were indeed involved in activities and programs at Mitra that were in accordance with the multiple intelligences they had. ABSTRAK Kecerdasan yang dimiliki manusia tidak hanya terbatas pada satu areal saja, tetapi terdiri dari beberapa kecerdasan atau dikenal dengan multiple intelligence. Ada 8 jenis kecerdasan menurut Howard Gardner, yaitu: Kecerdasan Linguistik; Kecerdasan logika matematika; Kecerdasan musical; Kecerdasan kinestetik; Kecerdasan visual spasial; Kecerdasan interpersonal; dan Kecerdasan naturalis. Kecerdasan yang dimiliki seseorang perlu dikembangkan secara maksimal, untuk pengembangan diri dan perencanaan masa depan. Untuk dapat mengembangkan kecerdasan tersebut, seseorang perlu terlebih dahulu menemukan dan mengenali kemampuan apa yang dimilikinya, salah satu caranya adalah dengan test Multiple intelligence. Melihat pentingnya mengenali kecerdasan yang dimiliki, maka Fakultas Psikologi – Universitas Tarumanagara – Jakarta bekerja sama dengan Panti Asuhan X (Mitra) mengadakan kegiatan test dan seminar Multiple intelligence. Tujuan kegiatan adalah : memetakan kecerdasan peserta selain untuk kepentingan pribadi peserta dan Mitra. sehingga Mitra dapat membuat program pembelajaran yang tepat disamping pembelajaran utama di sekolah. Hasil dari test ini nantinya akan dapat mengambarkan Multiple intelligence yang dimiliki masing-masing peserta. 3 hasil tertinggi adalah 3 Multiple intelligence yang dominan. Dari evaluasi kegiatan yang dilakukan, para peserta memberikan test imoni bahwa 3 skor terbesar dari test adalah sesuai dengan keadaan peserta, dan makin dikuatkan dengan skor test yang didapat. Mitra juga menjelaskan bahwa banyak juga diantara peserta yang memang terlibat dalam kegiatan dan program di Mitra yang sesuai dengan multiple intelligence yang dimiliki.